2019
DOI: 10.3390/genes11010038
|View full text |Cite
|
Sign up to set email alerts
|

Biomphalaria glabrata Granulin Increases Resistance to Schistosoma mansoni Infection in Several Biomphalaria Species and Induces the Production of Reactive Oxygen Species by Haemocytes

Abstract: Gastropod molluscs, which have co-evolved with parasitic digenean trematodes for millions of years, utilize circulating heamocytes as the primary method of containing and killing these invading parasites. In order to do so, they must generate suitable amounts of haemocytes that are properly armed to kill parasitic worms. One method by which they generate the haemocytes required to initiate the appropriate cell mediated immune response is via the production and post-translational processing of granulins. Granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These genes defined as granulocyte-specific were also found to be slightly over-expressed in cluster 1. Furthermore, if we look at some specific genes, found in a few rare articles defining a gene for a probable hemocyte population in Biomphalaria , such as granulin (BgGRN: BGLB011796), suspected to be expressed by some granulocyte subtypes ( 28 , 52 , 53 ), we notice that this gene seems to evolve along the pseudotime to be expressed by clusters 2 and 3. A gene that might be associated with granulin would be a toll-like receptor ( 54 ) that is found in our analyses to be expressed also by cells of cluster 2 ( Supplementary Figure 3 ).…”
Section: Resultsmentioning
confidence: 96%
“…These genes defined as granulocyte-specific were also found to be slightly over-expressed in cluster 1. Furthermore, if we look at some specific genes, found in a few rare articles defining a gene for a probable hemocyte population in Biomphalaria , such as granulin (BgGRN: BGLB011796), suspected to be expressed by some granulocyte subtypes ( 28 , 52 , 53 ), we notice that this gene seems to evolve along the pseudotime to be expressed by clusters 2 and 3. A gene that might be associated with granulin would be a toll-like receptor ( 54 ) that is found in our analyses to be expressed also by cells of cluster 2 ( Supplementary Figure 3 ).…”
Section: Resultsmentioning
confidence: 96%
“…Adhesion-related proteins, commonly implicated in bivalve immune responses and related to cell migration at the site of infection, were modulated: fibulin-1, hemicentin, cell adhesion molecule 3, lachesin (Gueguen et al, 2003;Xu and Faisal, 2008;Xu et al, 2018) and filamin A, which are also implicated in NF-kB and ROS responses (Muscolini et al, 2011;Uotila et al, 2017). Phagocytosis-related Tubby protein homolog and granulin are also implicated in effector actions against infection (Caberoy et al, 2010;Wu et al, 2018;Hambrook et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that cytotoxic molecules such as ROS and RNS are crucial for killing invading parasites in S. mansoni and support haemocyte-mediated damage and killing of miracidia of S. mansoni [ 33 , 84 ]. Conversely, S. mansoni cercariae may protect themselves from harmful oxidative environments in the host during the early stages of infection through some redox systems, such as glutathione (GSH) and Trx [ 85 ].…”
Section: Introductionmentioning
confidence: 99%